Экономические преступления в сфере информационных технологий или киберэкономические преступления - Игуменцева, Н. В.; Стеблянко, Б. А. (ХНУРЭ, 2014)
The number of crimes committed using the Internet is increasing. Criminalization of the Internet facilitates anonymity offender and the ability to remain at a distance of thousands of kilometers away from his victim. One of the dangerous consequences of the possible development of electronic payments is to destroy the system of combating money laundering, the existing banks. In this work we give a brief description assumes some important trends in the use of the Internet for economic crime
Keywords: экономические преступления; киберэкономические преступления; информационные технологии